Coral trophic pathways impact the allocation of carbon and nitrogen for egg development after bleaching - Jaffe, Melissa D.; Padilla-Gamiño, Jacqueline L.; Nunn, Brook L.; Rodrigues, Lisa J. (Frontiers in Ecology and Evolution, 2023)
The persistence of coral reefs requires the survival of adult coral colonies and their continued sexual reproduction despite thermal stress. To assess the trophic pathway (i.e., autotrophy and/or heterotrophy) used to develop gametes following bleaching, we thermally stressed Montipora capitata for one month at a time when corals in Hawai'i typically experience elevated seawater temperatures. After six and nine months of recovery, we pulse-chased non-bleached and previously bleached colonies using a dual-label design to compare the allocation of carbon and nitrogen at significant stages of gamete development. Dissolved inorganic carbon-(DI 13 C) and nitrogen-(DI 15 N) labelled seawater or 13 C-and 15 N-labelled rotifers were used to assess the autotrophic and heterotrophic pathways, respectively. At multiple time points for up to two years later, we collected adult coral fragments and isolated host tissue, Symbiodiniaceae cells, and developing eggs and captured gamete bundles to analyze their carbon (δ 13 C) and nitrogen (δ 15 N) stable isotopes. We found that the presence of Symbiodiniaceae was important for gametogenesis in both non-bleached and previously bleached colonies in two main ways. First, autotrophically-acquired carbon and nitrogen were both allocated to gametes during development, suggesting that recovery of photosynthesis after bleaching is critical for gametogenesis. Second, only heterotrophically-acquired nitrogen, not carbon, was incorporated into gametes and was readily recycled between host tissues and Symbiodiniaceae cells. This suggests that one of the purposes of heterotrophy following coral bleaching for M. capitata may be to supplement the nitrogen pool, providing available nutrients for endosymbiotic algal growth. Allocation of carbon and nitrogen to eggs coincided with the period when vertical transmission of symbionts to gametes occurs, further supporting the important relationship between gametogenesis and availability of Symbiodiniaceae for M. capitata.